Water Quality Assessment of Groundwater Resources in Nagpur Region (India) Based on WQI. Issue 3 (2009) - Rajankar, P. N.; Gulhane, S. R.; Tambekar, D. H.; Ramteke, D. S.; Wate, S. R.
Abstract : Water quality index (WQI) has been calculated for different groundwater sources i.e . dug wells, bore wells and tube wells at Khaperkheda region, Maharashtra (India). Twenty two different sites were selected in post monsoon, winter and summer season. And water quality index was calculated using water quality index calculator given by National Sanitation Foundation (NSF) information system. The calculated WQI showed fair water quality rating in post monsoon season which then changed to medium in summer and winter seasons for dug wells, but the bore wells and hand pumps showed medium water quality rating in all seasons where the quality was slightly differs in summer and winter season than post monsoon season, so the reasons to import water quality change and measures to be taken up in terms of groundwater quality management are required.